EFL University Students’ Perception of Using Smartphone in Learning Vocabulary - Johari, Johari; Yulianto, Yulianto; Sailun, Betty; Diana, Diana; Ayu, Fitri (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to discuss students' perceptions of the use of smartphone in learning new English vocabulary. An online questionnaire was used to obtain data from 34 of Indonesian EFL University students. The items of the questionnaire cover several aspects of vocabulary, including dictionary use, morphological analysis, and contextual analysis. Descriptive statistics of Likert-based questions were conducted to analyse the data. The findings of this study indicate that students perceive smartphone as facilitating several learning actions, such as contributing greatly to the acquisition of new English vocabulary, remembering, writing, and pronouncing words correctly. Apart from that, students also use smartphones because they are effective, especially in looking for synonyms and antonyms of words, thus really helping in the learning process. The findings of this study contribute to existing research on students' perceptions of the use of mobile applications for learning purposes, particularly in vocabulary learning.